If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -17 = -77 Reorder the terms: -17 + 5x = -77 Solving -17 + 5x = -77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 5x = -77 + 17 Combine like terms: -17 + 17 = 0 0 + 5x = -77 + 17 5x = -77 + 17 Combine like terms: -77 + 17 = -60 5x = -60 Divide each side by '5'. x = -12 Simplifying x = -12
| 16x^2-6x=-15 | | 26=20-ytimes-2 | | 8-8(8x-8)=(8x+8)8+8 | | 4x-7=9x+28 | | K/2-8=-3 | | (x+3)+(y-3)=16 | | 26=20-yx-2 | | -8j+3=-21 | | 9x-25=19x+294 | | f(x)=(x+1)(x+5)(5x-1) | | 6-5p=24 | | -44=6h-2 | | y=(45/)x−6 | | 7r-4=-13+r | | 24=4-2g | | (.5a/b)*.5a | | -5f+4=59 | | 0.00000131= | | 16+4e=48 | | r-5/12=19/12 | | 2r+yn=n-9h | | -1+3c=-4 | | (9x-6)(9x-6)-7=0 | | 6x+40=4x+200 | | 7b+8=22 | | 2n+yr=r-9h | | 4y-16=9y+200 | | (9x-6)-7=0 | | 4x^2-15x+21=0 | | F-3=-8 | | 6+e=19 | | 9y^3+54y^2-y-6=0 |